The Structure of Learning - Gardner, R.; Gardner, Beatrix (Psychology Press, 2013)
Drawing together research and theory in ethology and psychology, this book offers a clear and provocative account of the ways in which living organisms learn. Throughout, the authors' focus is on the importance of operational definition. In lively prose, describing experiments in enough depth to involve readers in the drama of experimental method, they recount the history of scientists' attempts to answer basic questions, and show how one study builds on another. Although they present the major traditional positions, they demand that readers examine actual evidence, recognize weaknesses, and consider alternatives. This critical process leads to the delineation of a bottom up, feed forward model in contrast to the traditional top down, feed backward one. Recent research in robotics and fuzzy logic suggests ways in which artificial as well as living systems pursue bottom up, feed forward ethological solutions to practical problems. The authors' extended discussion of their exciting work teaching sign language to chimpanzees vividly illustrates the application of the basic principles of learning elucidated in the book.